1988
DOI: 10.1093/oxfordjournals.humrep.a136744
|View full text |Cite
|
Sign up to set email alerts
|

LHRH agonists in IVF: different methods of utilization and comparison with previous ovulation stimulation treatments

Abstract: LHRH agonists are being increasingly used in ovulation stimulation protocols in IVF programmes. We have compared the results of two methods of utilization of LHRH agonists. In the long protocol, gonadotrophin stimulation was only commenced after a preliminary period of pituitary desensitization with LHRH agonist. In the short protocol, exogenous gonadotrophins were administered shortly after the start of LHRH agonist therapy, benefiting from the gonadotrophin flare-up effect. One-hundred-and-eighty-six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 0 publications
0
13
1
1
Order By: Relevance
“…In the ®rst month of the induction treatment 5±8 (6.8 average) ova reached the 20 mm size. This number is signi®cantly di erent from the numbers of mature follicles (3.9 and 4.2), obtained after long-term therapy with GnRH analog and hMG by Schmutzler et al [12] and Leyendecker et al [10], and slightly lower than the results of Frydman et al [5] who obtained in average 8.4 ova after the long-term protocol. Hyperstimulation wasn't ob-served during the study, so lutenization was performed in each case.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In the ®rst month of the induction treatment 5±8 (6.8 average) ova reached the 20 mm size. This number is signi®cantly di erent from the numbers of mature follicles (3.9 and 4.2), obtained after long-term therapy with GnRH analog and hMG by Schmutzler et al [12] and Leyendecker et al [10], and slightly lower than the results of Frydman et al [5] who obtained in average 8.4 ova after the long-term protocol. Hyperstimulation wasn't ob-served during the study, so lutenization was performed in each case.…”
Section: Discussioncontrasting
confidence: 66%
“…After homolog arti®cial therapy 15 (45%) patients became pregnant, and 3 of these pregnancies resulted in twins. This means a 25 and 27% e ciency rate following embryo-transfe r obtained by Leyendecker et al [10] and Frydman et al [5]. The 45% success rate is probably due mostly to the young age of the patients, the rebound e ect following inhibition, and the fact that no other causes of infertility apart from endometriosis were observed.…”
Section: Discussionmentioning
confidence: 88%
“…The major improvement attributed to analog use is the suppression of the endogenous LH surge in cycles, where pituitary suppression preceded ovarian stimulation [6,[11][12][13], It is well known that pituitary desensitization by buserelin does not occur in all cycles within 15 days [14]. This fact was used in our study to commence HMG administration only when definite desensitization was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The GnRH-a are currently used as a standard protocol in many IVF programs. However there are different protocols for GnRH-a; the two main protocols now used in the combined treatment of GnRH-a and human menopausal gonadotropin (HMG) are the 'short' and 'long' protocols [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies (Frydman et al, 1988a(Frydman et al, , 1988bHo et al, 2008) showed no difference in delivery rate between short and long GnRH agonist protocols.…”
Section: Introductionmentioning
confidence: 89%